A Proposal for Mitigating Fishermen Killing in Indian Sea Borders through Technology – Maritime Boundary Identification Device - Abhishek SN; Shriram K Vasudevan; Prashant R Nair; Thangavelu S; Sundaram RMD (Institute of Advanced Engineering and Science, 2017)
The Tamil Nadu – Sri Lanka maritime boundary has been responsible for frequent controversies in the global front, due to fishermen from Rameshwaram and Ramanthapuram districts recklessly straying past Indian waters. Instances of Indian fishermen being captured and killed by the Sri Lankan navy have spun vivid images of violence and human rights violation among the masses. Social activists are desperate for an automatic alarm system to warn the fishermen when they are about to cross the border, and avert a possible impending crisis. The following discussion focuses on the design of an alarm signal system that could alert the fishermen on a periodic basis as they approach closer to the maritime boundary. Installing Global Positioning System (GPS) devices would pose several economic challenges. Instead of the conventional approach of using GPS devices to track location, a transmitter – receiver system exquisitely designed to send signals to the boat would be effective. This system helps in keeping a continuous track of the boats. It provides a reliable solution to alert fishermen before they could inadvertently exceed the boundary.